Development of a continuous reactor for emulsion-based microencapsulation of hexyl acetate with a polyuria shell. (19th May 2019) - Gobert, Sven R. L.; Segers, Marleen; Luca, Stijn; Teixeira, Roberto F. A.; Kuhn, Simon; Braeken, Leen; Thomassen, Leen C. J.
Abstract: Microencapsulation is almost exclusively performed in batch processes. With today's chemistry increasingly performed in flow reactors, this work aims to realise a continuous reactor setup for the encapsulation of an ester with a polyuria (PU) shell. The generation of an emulsion template is performed in a recirculation loop driven by a pump and equipped with static mixers, screen type and Kenics ® . Calorimetric measurements are performed to characterise the energy dissipation rate inside the loop. The curing step is performed in a coiled tube reactor with two geometric configurations. Number based capsule size distributions are derived from micrograph analysis. Results indicate that the recycle pump is the main contributor to determine the capsule size distribution. A continuous setup is achieved for PU microcapsules containing hexyl acetate with a production rate of 198 g/h dry capsules, and a mean capsule diameter of 13.3 µm with a core content of 54 wt%.